Exploring the Emotional Reaction of Mental Health Professional in Related to Stigma on People with Mental Health Problems in Saudi Arabia - Alyousef,, Dr. Seham Mansour, (International Journal of Innovative Research in Medical Science, 2017)
People’s beliefs on people with mental health problems set the stage for how they interact with, provide opportunities for, and help support a person with mental health issue in mental health care services. Of concern is the prevalence of these beliefs and emotional among professional mental health workers, which are also embedded in Saudi Arabian culture and the community in the KSA. The present study aimed to assess the application of the concept of stigma; will focus on professional’s emotional reaction on people with mental health problems in mental health care services. Overall, stigma is defined as a cultural and professional phenomenon that manifests at both a structural and individual level. A quantitative approach was applied and data was collected a total of 50 mental health care professionals, men and women in different health professions, via the emotional reactions Scale on mental illness short form which tested in several studies worldwide. Data was analysed using SPSS. The reliability of the scale was evaluated by measuring internal consistency using SPSS. Participants also completed a demographic data sheet. The findings of the present study point to the significant convergent between emotional reactions exhibited with regard to people with mental health problems. Significant statistical differences exist between the five different specialist groups [F (11.646); p=. 000<0.05]. When analysing the results of the dimension reduction factors, two component factors existed regarding attitude attribution test. The high scores of each component affected the results with stigma analysis; ‘exclusion’, ‘rejection and caution’